Microstructure and activity of platinized CdS-Al2O3 photocatalysts for reduction of water to hydrogen by visible light - Sinha A.S.K.; Sahu N.; Upadhyay S.N. (My University, 2025)
Alumina supported Pt-CdS is an effective photocatalyst for the reduction of water to hydrogen using visible light. The activity is dependent on the method of incorporation of platinum on the catalyst. The catalysts were characterized by XRD, XPS, H2 chemisorption, temperature programmed oxidation and optical spectroscopy. The results show that the band gap of CdS has no correlation with the activity. Crystallite size of CdS and the nature of contact between alumina and CdS, however, affect the activity. Platinum on the surface of the catalyst is in the form of Pt-PtSx.